2019
DOI: 10.1080/00016357.2018.1564837
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Jönköping dental fear coping model: a patient perspective

Abstract: Objective: This study is a part of a project with the aim to construct and evaluate a structured treatment model (the J€ onk€ oping Dental Fear Coping Model, DFCM) for the treatment of dental patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…None of the studies exploring how CBT applied by dental practitioners [26][27][28][29] investigate the role change required by those practitioners to attend to patient's psychological needs. This new role, a change from focusing on mouth pathologies to anxiety triggers, is outside the remit or competence of most dental practitioners since psychology is not a required subject in dental schools [32,33]. It is also potentially problematic; the culture of dental care being influenced by performance-led actions rather than relational aspects.…”
Section: Introductionmentioning
confidence: 99%
“…None of the studies exploring how CBT applied by dental practitioners [26][27][28][29] investigate the role change required by those practitioners to attend to patient's psychological needs. This new role, a change from focusing on mouth pathologies to anxiety triggers, is outside the remit or competence of most dental practitioners since psychology is not a required subject in dental schools [32,33]. It is also potentially problematic; the culture of dental care being influenced by performance-led actions rather than relational aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Dentophobia, also known as odontophobia, is defined as the fear of dental interventions that originates from the wrong assumption that these interventions are harmful and dangerous (1). Studies show that 10 -27% of adults experience moderate to high levels of dental anxiety, and 4 -6% of them suffer from dentophobia (2,3). It has also been shown that the prevalence of dentophobia is almost stable over time (4,5).…”
Section: Introductionmentioning
confidence: 99%